RANS simulation of open propeller dynamic loads in regular head waves considering coupled oblique-flow and free-surface effect. (15th August 2021) - Zhang, Wencan; Ma, Ning; Gu, Xiechong; Feng, Peiyuan
Abstract: To offer references for ventilation and load fluctuation of propeller in actual seaway, this paper presents a RANS (Reynolds-Averaged Navier-Stokes equations) investigation on open propeller dynamic loads in regular head waves at variant submergence depths, from the perspective of the coupled oblique-flow and free-surface effect. Discussions are made concerning the dynamic integral loads and single-blade loads (both axial and in-plane), and instantaneous single-blade loads at different azimuthal positions. CFD (Computational Fluid Dynamics) verification and validation are conducted based on an experiment in calm water and regular head waves conducted in a circulating water channel. As conclusions, under fully-submerged condition, single-blade load variations are related solely to the unsteady oblique-flow environment, with shifts of azimuthal positions corresponding to the maximum and minimum thrust and torque due to inflow non-uniformity. Under periodical-emerging condition, high-frequency integral-load fluctuations are identified by both simulation and experiment, resulting from the enhanced propeller-surface interactions due to upward wake inclination; this enhanced propeller-surface interaction also causes serious ventilation, abrupt rises or drops of axial single-blade loads, and destruction and dissipation of propeller vortex system. Furthermore, the self-induction effect on the load distribution non-uniformity is found to be unobvious in regular waves due to the unsteady and non-uniform inflow environment. Highlights: Investigation on the propeller dynamic loads in waves considering the coupled free-surface and oblique-flow effect. As the periodically-emerging propeller approaches the wave crest, high-frequency thrust fluctuation and vortex destruction are identified. Under full submergence, minor shifts of azimuthal positions of maximum/minimum single-blade loads occur. Self-induction effect is found to be unobvious in regular waves.